Uma vez cesárea, sempre cesárea?: representações sociais de mulheres com uma cesárea em gestação anterior sobre o parto normal - Adrinez Cançado e Nascimento (2013)
This study addresses the ways of thinking, feeling and acting of women with a previous cesarean over a vaginal delivery. Considering the expressive cesarean rates, its recrudescence worldwide and the importance of cesarean indications because of a previous cesarean in the keeping of these rates, the proposal of this study was built having the following tensions: on the one hand the strength of the belief that oncecesarean, always cesarean in the social set, its symbolic vigor , kept by lack of information; the determination of previous pregnancies in the way women are going to deal with future pregnancies and, on the other hand, the possibility of having a vaginal delivery after a cesarean, as scientific evidences point out, with benefits for both mother and infant, setting an investigation that is inserted in a context of challenges. The objective is to understand the social representation of women with a previous cesarean over a vaginal delivery. It was employed a qualitative approach with a theoretical orientation of the Theory of Social Representations in the perspective proposed by Serge Moscovici, carried out in two maternity hospitals, which render exclusive service to the National Health System, in Belo Horizonte, Minas Gerais, Brazil. In this study thirty one puerperal women who had vaginal delivery as a via of present delivery that, in a previous experience, had cesarean delivery and who accomplished the requirements for the criteria of inclusion in the research, took part. The data were collected between 09/03/2012 and 27/04/2012, through open interview. The reports were analyzed in accordance with the analyses technique of thematic content proposed by Bardin. The research was approved by the Ethics Research Committee of the Federal University ofMinas Gerais and by the institutions where the study was carried out. The informed consent form was signed by all participants. Two empirical categories were identified: a) The presence of the strange: journey of women with a previous cesarean facing a vaginal delivery and b) the experience of a vaginal delivery after a previous cesarean: Redefinition of thinking, feeling and acting of women who, at present, are at the analyses stage. The first refers to the representations about a vaginal delivery, during pregnancy or right before delivery, of women who had a previous cesarean and who are informed of the possibility of a vaginal delivery. The second category shows the social representations at the time of the interview, after having experienced the delivery. From these categories, it was noticed that that are transformations and reconstructions in the knowledge of women regarding delivery, caused mainly by the experience of a vaginal delivery. It is expected that this study provides reflections that contribute to the configuration of a public policy which enhances women knowledge helping them deconstruct the deeply rooted knowledge in rigid social structures and in the reconfiguration of new knowledge which favor the experience of pregnancy, delivery and birth without conflicts of this kind. This study is also expected to impact positively in the reduction of cesarean rates in Brazil.